2015
DOI: 10.1111/ejn.13087
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of perception and action in audiovisual multisensory integration

Abstract: The “temporal rule” of multisensory integration proposes that unisensory stimuli, and the neuronal responses they evoke, must fall within a window of integration. Ecological validity demands that multisensory integration should occur only for physically simultaneous events (which may give rise to non-simultaneous neural activations), and spurious neural response simultaneities unrelated to environmental multisensory occurrences must somehow be rejected. Two experiments investigated the requirements of simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 52 publications
3
19
1
Order By: Relevance
“…Overall, these results are reminiscent of findings by Leone and McCourt ( 2013 , 2015 ), who manipulated auditory and visual stimulus intensity, as well as stimulus timing, to measure the effects of physical and physiological simultaneity on multisensory gain. Using violations of the race model inequality as an indicator of multisensory gain, they found that despite significant differences in RT to unisensory stimuli that resulted from variations in stimulus intensity (i.e., more intense stimuli resulted in faster RTs), multisensory gain was restricted to a narrow range of SOAs within 50 ms of simultaneity (see also van der Stoep et al 2015b ).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Overall, these results are reminiscent of findings by Leone and McCourt ( 2013 , 2015 ), who manipulated auditory and visual stimulus intensity, as well as stimulus timing, to measure the effects of physical and physiological simultaneity on multisensory gain. Using violations of the race model inequality as an indicator of multisensory gain, they found that despite significant differences in RT to unisensory stimuli that resulted from variations in stimulus intensity (i.e., more intense stimuli resulted in faster RTs), multisensory gain was restricted to a narrow range of SOAs within 50 ms of simultaneity (see also van der Stoep et al 2015b ).…”
Section: Discussionsupporting
confidence: 67%
“…Taken together, the results seemingly indicate that the SJ and MRT tasks likely index partially dependent multisensory processes that are somewhat dissociable and more readily indexed when considering relatively larger inter-subject variability (see Leone and McCourt 2015 ; Harrar et al 2016 , for a similar argument). In other words, while an opposing relationship between multisensory binding and gain as a function of distance is not necessarily evidenced in group-level measures, this relation becomes more apparent at an individual subject level (when controlling for intra-subject variability).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We suggest that in order to correctly bind information emanating from a common source, the neural processing scheme may allow for a greater temporal lead by the part of the sensory modality for which the native reference frame has been misaligned with respect to the body (and thus may require additional processing time). That is, we conjecture that the computation performed in order to make SJs may adapt as to correct for physiological lags due to reference frame transformation/reconciliation (see Leone & McCourt, 2013 , 2015 , for a similar argument). In the second experiment, we test this prediction by dissociating either the auditory or the visual reference frame with respect to the body-centered reference frame.…”
Section: Methodsmentioning
confidence: 96%
“…This V shape is illustrated in Figure 1 , showing results from our literature survey on reaction times to audiovisual stimuli as a function of SOA. Only studies that used equivalent task conditions were included in this figure (for additional relevant research on SOA, see Harrar, Harris, & Spence, 2017 ; Leone & McCourt, 2015 ; Van der Stoep, Spence, Nijboer, & Van der Stigchel, 2015 ). Each subfigure shows mean reaction times as a function of SOA, where a negative SOA value means that the onset of the visual stimulus occurred after the onset of the auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%